Effect of Ketapang Leaf Extract on HDL Levels of Rattus norvegicus Induced by High-fat Foods - Nurfadly, Nurfadly; Fajar, Muhammad; Thristy, Isra; Yenita, Yenita (Universitas Islam Bandung, 2024)
High-density lipoprotein (HDL) functions to transport cholesterol from the blood vessel endothelium to the liver and excreted through the digestive tract so that it does not cause dyslipidemia, which is a risk factor for cardiovascular disease. Current treatment for dyslipidemia uses long-term statin drugs, which can cause various side effects, so herbal alternatives such as ketapang leaves (Terminalia catappa L.), which contain flavonoids and have the effect of increasing HDL levels, needed to be evaluated to achieve that reason. This study aims to evaluate whether ketapang leaf extract has an effect on increasing blood HDL levels. This research used experimental animals with a pretest and a posttest with a control group design. It was conducted at the Biochemistry Laboratory and Laboratory Animal Management Unit, Faculty of Medicine, Universitas Muhammadiyah Sumatera Utara, Medan, from September to December 2023. This study used Wistar strain male white rats (Rattus norvegicus) that were induced on a high-fat diet, divided into five groups: negative control, positive control (given simvastatin), treatment 1 (given 21 mg/kgBW ketapang leaf extract), treatment 2 (given 42 mg/kgBW ketapang leaf extract) and treatment 3 (given 84 mg/kgBW ketapang leaf extract). The study results showed a significant difference (p<0.05) in the average HDL levels before and after treatment in the positive control, treatment 2, and therapy three groups. Thus, the study concluded that ketapang leaf extract affected increasing HDL levels of male white rats (Rattus norvegicus).